Extractive Spectrophotometric Determination of Cu(II) with Phosphoryl Derivative of p-tert-butylthiacalix(4)arene - LOKHANDE, R.S.; R. SHARMA, MANOJ; CHOUDHARY, A.B. (Asian Journal of Chemistry, 2010)
A spectrophotometric method has been developed for the determination of Cu(II) using a phosphoryl derivative of p-tert-butylthiacalix(4)arene as an extractive reagent. The reagent forms a coloured complex, which has been quantitatively extracted in toluene at pH 8.3. The method obeys Beer’s law over a range from 1 to 19 ppm. The molar absorptivity and Sandell sensitivity were 1.046 × 103 L mol-1 cm-1 and 1.6 × 10-5 μg cm-2, respectively. The proposed method is very sensitive and selective. The method has been successfully applied to synthetic and commercial samples.